Metrology for ambient mass spectrometry - Salter, Tara La Roche (2015)
Ambient mass spectrometry (AMS) is a new and versatile method for analysing a multitude of different sample types with the benefit of analysis at ambient pressure and the many other advantages that this entails. However, as these techniques are still in their infancy, metrological development of the techniques is essential. This is a critical step before AMS can be used reliably in the application areas in which it has shown great promise. The research in this thesis addresses the development of AMS sources, in particular plasma-assisted desorption-ionisation, PADI. Optimisation and characterisation is fundamental to understanding and developing the technique.